Evaluation of the MOD16A2 evapotranspiration product in an agricultural area of Argentina, the Pampas region - Degano, María Florencia (2021)
The Pampas Region is a big plain of approximately 520,000 km2 in Argentina. It is essential to estimate evapotranspiration (ET) in this region since the primary productivity is directly linked to water availability. Information provided by satellite missions allows monitoring the spatial and temporal variability of ET. In the current study, we evaluated the version 006 of MOD16A2 product (MOD16A2.006) of Potential Evapotranspiration (ETp) and Actual Evapotranspiration (ETa) in Argentinian Pampas Region (APR). MOD16A2.006 product was compared with Crop Evapotranspiration (ETc), calculated with local measurements from the Oficina de Riesgo Agropecuario (ORA), and Crop Coefficient (Kc) data (function of Normalized Difference Vegetation Index (NDVI)) in seven stations in the APR from 2009 to 2018. We evaluated ETa at two temporal scales: accumulated values (mm) per growth stages (soybean crop), and 8-day accumulated values (mm8d−1). The results showed a systematic overestimation around 65% for ETp(MOD16A2.006) (found and eliminated by means of a linear function) and underestimation (in most stations) for ETa(MOD16A2.006) in accumulated values per growth stages. Respect to mm8d−1, no systematic error was observed, but the relationship ETa(ORA) − ETa(MOD16A2.006) for soybean crop behaves similarly throughout APR.